Modeling magmatic intrusion’s effects on the geoid and vertical deflection. Application to Lanzarote, Canary Islands, and Long Valley Caldera, California. - Charco, M.; Sevilla, M. J.; Rundle, J. B.; Fernández, J. (Física de la Tierra, 2002)
Volcanic activity produces ground deformation and gravity changes in response to geodynamic processes within the crust. Many of these precursors are measurable with present-day technology like precise surveying techniques or “high-technology” as those use in satellite-based geodesy (e.g. Global Positioning System). It is usually assume that vertical deflection and geoid height needed for comparing such as techniques, are not significantly affected by the intrusion process. In this work, we have tested theoretically this assumption and applied to active zones with different crustal structures that resemble layered media, namely Lanzarote (Canary Islands, Spain) and Long Valley Caldera (California). Considering the geoid as an equipotential surface of the gravitational field we have used the elastic-gravitational deformation model, proposed by Rundle and Fernández, to compute geoid and vertical eflection changes produced by a magmatic intrusion in the crust. This echnique represents the geoid and vertical deflection due to a point source, hich therefore can be sed s Green’s function with which to convolve an rbitrary distribution of subsurface mass or pressure hange. The results show hat the magma intrusion radius should be of approximately 1 km for the ffects on both geoid undulations and vertical deflection not to be negligible. This radius would decrease for shallow intrusions. The pressure effects omputed with the model, if e considered realistic pressure changes values, ould be always negligible.